Implementing the PBL Model to Improve Students' Mathematical Problem Solving Ability at Medan State Junior High School - Dian Anjeli Siregar; Denny Haris; Hasiholan Sitompul (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to find out: (1) what efforts are being made to improve the mathematical problem-solving skills of students in class XI, IPS 1, of Medan 7 State Senior High School through a problem-based learning model; and (2) how to improve students' mathematical problem-solving skills in class XI, IPS 1, of Medan 7 State Senior High School after applying the problem-based learning model. This type of research is called "classroom action research," which is carried out in two cycles, each of which is carried out in two meetings. The subjects in this study were 35 students in class XI at Medan 7 State Senior High School. The data collection techniques used were teacher and student observation sheets and tests of mathematical problem-solving abilities. The test was carried out three times: the initial test, the ability test to solve mathematical problems I, and the ability test to solve mathematical problems II. The findings of this study show that: (1) students' mathematical problem-solving abilities were assessed before being given action, with as many as 3 students (8.57%) achieving learning mastery and 32 students (91.42%) not achieving learning mastery. (2) After being given action in cycle I, it was found that 19 students (54.28%) had achieved learning mastery and 16 students (44.71%) had not reached the learning mastery level. (3) In cycle II, 31 students (88.57%) achieved mastery learning, while 4 students (11.429%) did not achieve mastery learning, resulting in a 34.29% increase from cycle I to cycle II.